Moderation of the Association Between Individual Food Security and Poor Mental Health by the Local Food Environment Among Adult Residents of Flint, Michigan - Rachel S. Bergmans; Richard C. Sadler; Julia A. Wolfson; Andrew D. Jones; Daniel Kruger (Mary Ann Liebert, 2019)
Purpose: Food insecurity is a psychosocial stressor with deleterious effects on mental health. This study examined whether the local food environment moderates the association of individual food insecurity with poor mental health. Methods: Cross-sectional survey data were collected from adult residents of Flint, Michigan (n=291), in 2015. Multivariate logistic models assessed whether quality of the local food environment moderated the relationship of food insecurity with poor mental health. A binary indicator of poor mental health was created. Participants were asked to rate their overall ?mental or emotional health? using a 5-point Likert scale. Individuals were classified as having either good mental health (i.e., ratings of good, very good, or excellent) or poor mental health (i.e., ratings of fair or poor). Results: In fully adjusted models, food insecurity was associated with 3.2 (95% confidence interval [CI]: 1.6?6.2) times higher odds of poor mental health. However, increased proximate access to vegetables and fruits moderated this association. For example, those in the bottom 25th percentile of access to vegetables had 7.4 (95% CI: 2.7?20.5) times higher odds of poor mental health. In contrast, for those in the top 25th percentile of vegetable access, food insecurity was only marginally associated with poor mental health (odds ratio=2.2; 95% CI: 1.0?4.7). Conclusion: Greater proximate access to vegetables and fruits moderated food insecurity's association with poor mental health. Longitudinal evaluation of programs and policies that improve availability of nutrient-rich foods in food insecure communities is needed to determine whether they yield a mental health benefit.